Gae mi heo li - Heo, Eun Mi (Yes nal yes jeog e, 2007)
Once upon a time, ants relied upon a rabbit to survive. One day the rabbit thought of the idea how to free itself from the ants. Now we can explore why the ant's waist is so tiny